Reinforcing European Defence Industry for Times of Great Power Conflicts - Csiki Varga, Tamás (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
With the European security environment deteriorating and destabilising in the 2010s, European defence – particularly the European defence industry – has gained heightened attention since 2022, as evidenced by Russia’s renewed aggression towards Ukraine. European countries have since attempted to efficiently address the dilemma of short-term production and stock replenishment versus long-term research, development, and innovation to offset the unpreparedness of European armed forces to fight protracted high-intensity wars. Accordingly, this chapter aims to outline the demand–supply equation of the European defence industry leading up to the Hungarian EU Presidency in 2024, and the adoption of the first-ever European Defence Industrial Strategy. This strategy aims to identify the drivers for developing the European Defence Industrial and Technological Base (EDTIB) as a defence ecosystem by the 2030s, enabling the sustainable provision of arms that European countries may need to defend themselves on European soil and uphold their interests. The following analysis provides an overview of the trends leading up to 2024 for enhancing European defence industrial production, research and development. The chapter is structured as follows: first, it outlines the dynamics of the changing European security environment and threat perception, followed by an assessment of European capability gaps and policy responses aimed at closing these gaps, including an improved record of defence investments. The main argument is that despite the constraints of EDTIB in the early 2020s, such as the effects of three decades of underinvestment, fragmentation of production capacities, shortcomings in providing raw materials and access to cutting-edge technology, as well as shortages of manufacturing capabilities and skilled manpower, there are nevertheless opportunities to remedy this situation. Drivers for comprehensive and efficient European defence industrial cooperation are being developed, including better-aligned strategic planning and defence capability development, currently underpinned by increasing defence spending, extensive joint defence procurements, and research and development (through the European Defence Industry Reinforcement through Common Procurement Act and the European Defence Industry Programme, supported by Permanent Structured Cooperation, the European Defence Fund, and the European Peace Facility).Keywords: defence industry, strategy, armament, procurement, European Defence Technological and Industrial Base